Analysis of occupational injuries among workers in foundry workshops - A. M. Lazarenkov; I. A. Ivanov; M. A. Sadokha; A. A. Novik (Литьë и металлургия, 2024)
The results of the analysis of occupational injuries among workers in foundry workshops with different types of production are presented. It is shown that the highest number of accidents by location occurs in the fettling‑cleaning, molding, and meltingpouring areas of foundry workshops, and the most hazardous professions are those of fettler, molder, melter, pourer, and repair fitter. An analysis of the causes of injuries in foundry workshops showed that about 76 % of cases occur due to organizational reasons, about 16 % due to technical reasons, about 6 % due to sanitary‑hygienic reasons, and about 2 % due to psychophysiological reasons. The possibility of predicting injury rates among workers in foundry workshops is demonstrated.